2008
DOI: 10.3103/s1068375508040054
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the opportunity for increasing the yield of hydrogen peroxide in plasma-solution systems

Abstract: The influence of the addition of alcohol (ethanol and propanol-2) to an electrolyte solution on hydrogen peroxide formation under the action of glow and gliding discharges of atmospheric pressure was studied. The addition of alcohol up to 0.1 mol/l was found to increase the yield of H 2 O 2 significantly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 8 publications
0
13
1
Order By: Relevance
“…The addition of t-butanol, which is a scavenger of •OH-radicals, resulted in the decrease in the phenol decomposition degree May, 2016 [1]. At the same time, the addition of alcohols (ethanol and 2-propanol) in the optimal amount (up to 0.1 mol/l) increased the hydrogen peroxide concentrations in glow discharge over water [27]. The ratio between the rates of these reactions will define the behavior of H 2 O 2 concentration.…”
Section: H 5 Oh+•oh→h 2 O+•c 6 H 4 Oh •C 6 H 4 Oh+•oh→c 6 H 4 (Omentioning
confidence: 92%
“…The addition of t-butanol, which is a scavenger of •OH-radicals, resulted in the decrease in the phenol decomposition degree May, 2016 [1]. At the same time, the addition of alcohols (ethanol and 2-propanol) in the optimal amount (up to 0.1 mol/l) increased the hydrogen peroxide concentrations in glow discharge over water [27]. The ratio between the rates of these reactions will define the behavior of H 2 O 2 concentration.…”
Section: H 5 Oh+•oh→h 2 O+•c 6 H 4 Oh •C 6 H 4 Oh+•oh→c 6 H 4 (Omentioning
confidence: 92%
“…The electrode material, in the case of both a glow discharge [7] and a diaphragm discharge, influences the formation of H 2 O 2 in the solution. In Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The accumulation of hydrogen peroxide in the solution under the action of the gas discharges was measured with the help of spectrophotometric analysis (the scheme of the experimental setup is presented in [7], and λ = 253.7 nm) and also with the help of iodine titration with molybdate ammonium.…”
Section: Methodsmentioning
confidence: 99%
“…Liu et al [10] used a glow-like discharge plasma device to treat a sodium lactate solution, and the yield of hydrogen peroxide in activated sodium lactate is eight times higher than that of the PAW, reaching 325 μmol/L. Kuz'micheva et al [11] found that the yield of H 2 O 2 increased from 5:2 � 10 −4 mol=L to 1:4 � 10 −3 mol=L when glow discharge plasma was used to treat 0.01 mol/L Na 2 SO 4 and 0.1 mol/L ethanol mixed solution compared with only 0.01 mol/L Na 2 SO 4 . In our previous study [12], a DC-driven air plasma device has been used to treat solution containing H+, NO − 2 and NO − 3 species and achieved a better decontamination effect than PAW.…”
Section: Introductionmentioning
confidence: 99%